Caracterização físico-química e capacidade antioxidante de pitanga (Eugenia uniflora L.) - Bagetti, Milena (2009)
Due to the scarce amount of studies on the physicochemical composition and antioxidant capacity of pitanga fruits (Eugenia uniflora L.) this study was performed, with objective of increase data on pitanga fruits from Rio Grande do Sul state (Brazil) by determining the composition and antioxidant capacity of flesh and seeds from pitanga. We analyzed pitanga fruits with different flesh colors (purple, red and orange) from tree selections cultivated at Embrapa Clima Temperado (RS-Brazil). The quality parameters of pitanga fruits (pH, brix, acidity) were within the legal limits established for frozen pulp and only slight differences were observed in these parameters and in the proximate and fatty acid composition among fruits with different flesh color. Orange fleshed pitanga had higher carotenoid content than red samples. The extracts from purple fleshed color pitanga had the highest total phenolic and anthocyanin content along with the highest antioxidant capacity. Antioxidant capacity (DPPH and FRAP assay) of methanolic pitanga extracts was highly correlated to the total phenolic content, but in ethanolic extracts anthocyanin content was correlated only to FRAP antioxidant capacity. These results indicate that pitanga cultivated in the Rio Grande do Sul state, specially the purple fleshed fruits, can be considered sources of bioactive compounds. Pitanga seeds had antioxidant capacity that was partially correlated to their high phenolic content and showed some variation according to the pitanga flesh colors. Accordingly, we suggest that this low value waste of pitanga processing, could be used as a source of natural antioxidants. No relevant differences were found in the proximate composition among seeds from pitanga of different colors. Results revealed that pitanga seeds are a good source of dietary fiber, which could be explored for use in animal and/or human nutrition. However, more studies are necessary to determine if some antinutritional factor like cyanogenic glycosides could be a limit for this application.